Activation of the pattern recognition receptor NOD1 in periodontitis impairs the osteogenic capacity of human periodontal ligament stem cells via p38/MAPK signalling. Issue 12 (31st August 2022) - He, Yuying; Wu, Zuping; Chen, Sirui; Wang, Jiahe; Zhu, Li; Xie, Jing; Zhou, Chenchen; Zou, Shujuan
Abstract: Objectives: Nucleotide oligomerization domain receptor 1 (NOD1) mediates host recognition of pathogenic bacteria in periodontium. However, the specific role of NOD1 in regulating osteogenesis is unclear. Therefore, this study focused on the activation status of NOD1 in periodontitis and its effect on the osteogenic capacity of human periodontal ligament stem cells (hPDLSCs) as well as the underlying mechanism. Methods: Histological staining and Western blot were utilized to assess NOD1 expression in the periodontium of people with or without periodontitis. HPDLSCs were cultured under NOD1 agonist or antagonist treatment. Q‐PCR and Western blot were employed to assess the expression of osteogenic marker genes and proteins. Alizarin red staining and alkaline phosphatase staining were used to determine the osteogenic capability of hPDLSCs. The activation of downstream signalling was determined and specific inhibitors were utilized to confirm the signalling pathway in NOD1‐regulated osteogenesis. Results: NOD1 expression is significantly elevated in periodontitis. With NOD1 activated by particular agonist tri‐DAP, the osteogenic potential of hPDLSCs was impaired. NOD1 antagonist co‐incubation partially restored the decreased osteogenesis in hPDLSCs. P38/MAPK was phosphorylated in tri‐DAP‐induced NOD1 activation. The inhibitor of p38 rescued the suppression of osteogenesis induced by tri‐DAP in hPDLSCs. Conclusions: Our study revealed the expression status of NOD1 in periodontitis. Its activation greatly decreased the osteogenic capacity of hPDLSCs which was mediated by the phosphorylation of p38 downstream signalling. Abstract : Nucleotide oligomerization domain receptor 1 (NOD1) is substantially expressed in periodontium of individuals with chronic periodontitis. Abnormal activation of NOD1 may result in alveolar bone loss by impairing the osteogenic potential of human periodontal ligament stem cells, which provides a potential target in periodontium regeneration.